(untitled) (The Science Post, 2025)
Cardiovascular disease (CVD) continues to dominate global mortality statistics despite extensive clinical research and therapeutic development. Early and accurate detection remains the cornerstone of effective intervention. However, diagnostic methods often fall short due to limitations in accessibility, invasiveness, and predictive power. This paper reframes cardiovascular diagnostics by exploring both theoretical foundations and recent technological advances. We analyze classical and contemporary diagnostic models through the lens of health systems theory, behavioral models, and computational decision-making. Parallelly, we evaluate transformative technologies—ranging from AI-assisted imaging and wearable sensors to molecular diagnostics and remote monitoring systems—that challenge traditional paradigms. Together, these insights illustrate a shifting landscape in which multidisciplinary approaches drive more timely, precise, and personalized cardiac care.